PERKEMBANGAN KARAKTER PESERTA DIDIK SEKOLAH DASAR DI ERA DIGITAL: SYSTEMATIC LITERATURE REVIEW - Vita Meitria; Pipit Athyana Isniasih; Murfiah Dewi Wulandari; Darsinah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the character development of elementary school students in the digital era through a Systematic Literature Review (SLR) approach. The review was conducted following PRISMA guidelines on articles published between 2022 and 2026, sourced from Scopus, ERIC, ScienceDirect, DOAJ, and Google Scholar. A total of 34 articles met the inclusion criteria and were analyzed comprehensively. The findings indicate that the digital era offers significant opportunities for character development, particularly in responsibility, independence, creativity, collaboration, and critical thinking. The use of digital technology, social media, learning platforms, and artificial intelligence can effectively support character internalization when implemented appropriately. However, the digital era also presents challenges, including exposure to negative content, reduced face-to-face social interaction, increasing individualism, and the risk of moral degradation. Teachers, parents, and schools play essential roles in optimizing character education within digital environments. Strong collaboration among families, schools, and adaptive technology utilization is necessary to foster a generation that is morally grounded, digitally literate, and well-prepared to face the challenges of the twenty-first century wisely, responsibly, and ethically.